2016
DOI: 10.3390/ijms17071013
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Potentiates Anabolic Effects of Exogenous Hyaluronic Acid in Rat Articular Cartilage

Abstract: Hyaluronic acid (HA) is used clinically to treat osteoarthritis (OA), but its pharmacological effects under hypoxic conditions remain unclear. Articular chondrocytes in patients with OA are exposed to a hypoxic environment. This study investigated whether hypoxia could potentiate the anabolic effects of exogenous HA in rat articular cartilage and whether these mechanisms involved HA receptors. HA under hypoxic conditions significantly enhanced the expression of extracellular matrix genes and proteins in explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Hyaluronic acid is composed of N -acetylglucosamine and d -glucuronic acid, which are linked via β-(1,3) bonds through dehydration polymerization. It is a major component of the ECM in connective tissue such as skin and eye lens and is used clinically to treat osteoarthritis [12]. As the HA polymer chain carries substantial negative charges, the molecules of HA completely unfold in water due to charge repulsion, occupying considerable space and enabling HA to absorb water 1000 times its own weight [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid is composed of N -acetylglucosamine and d -glucuronic acid, which are linked via β-(1,3) bonds through dehydration polymerization. It is a major component of the ECM in connective tissue such as skin and eye lens and is used clinically to treat osteoarthritis [12]. As the HA polymer chain carries substantial negative charges, the molecules of HA completely unfold in water due to charge repulsion, occupying considerable space and enabling HA to absorb water 1000 times its own weight [13].…”
Section: Introductionmentioning
confidence: 99%
“…CD44, plays an important role in regulating multiple cellular functions (Ishida et al, 1997). It has previously been shown that hypoxia potentiated the anabolic effects of HA, including the redifferentiation of articular chondrocytes and synthesis of ECM, through enhancing CD44 expression and binding affinity (Ichimaru et al, 2016). Furthermore, previous research suggested that hypoxia could enhance the expression of CD44 via HIF-1α (Liang et al, 2017).…”
mentioning
confidence: 99%
“…With the development of tissue engineering technology, implantation of HA-based hydrogel is a novel biological treatment for early stage IDD. Various HA hydrogels have been investigated for their potential to replace and regenerate the NP through reducing inflammation response and nociceptive behaviour (Isa et al, 2015;Mohd et al, 2018), promoting ECM synthesis (Kim et al, 2015), and restoring biomechanical properties (Zhou et al, 2014). Furthermore, it has recently been shown that HA hydrogels could promote stem cell differentiation to NP-like cells and improve the efficacy of stem cells for NP regeneration (Chen et al, 2019;Peroglio et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bioactivity of HMW‐HA for chondrocytes and synoviocytes have been studied, and the activity of HA has been shown to depend on its molecular weight. For instance, HA with a molecular weight (Mw) larger than approximately 7.0 × 10 5 to 8.0 × 10 5 Da enhanced the biosynthesis of the extra‐cellular matrix and the sensitivity to growth factor, whereas the expressions of some catabolic factors such as matrix metalloproteinases (MMPs) and inflammatory cytokines were suppressed in in vitro and in vivo experiments . These biological effects of HA are generally attributed to the stimulation of target cells via binding to HA receptors such as CD44.…”
Section: Introductionmentioning
confidence: 99%